2016
DOI: 10.3847/0004-637x/819/2/156
|View full text |Cite
|
Sign up to set email alerts
|

MULTIWAVELENGTH STUDY OF QUIESCENT STATES OF Mrk 421 WITH UNPRECEDENTED HARD X-RAY COVERAGE PROVIDED BY NuSTAR IN 2013

Abstract: We present coordinated multiwavelength observations of the bright, nearby BL Lacertae object Mrk 421 taken in 2013 January-March, involving GASP-WEBT, Swift, NuSTAR, Fermi-LAT, MAGIC, VERITAS, and other collaborations and instruments, providing data from radio to very high energy(VHE) γ-ray bands. NuSTAR yielded previously unattainable sensitivity in the 3-79keV range, revealing that the spectrum softens when the source is dimmer until the X-ray spectral shape saturates into a steep 3 G » power law, with no … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
98
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 104 publications
11
98
2
Order By: Relevance
“…Gorham et al (2000) estimated the central black hole mass of order ∼ 10 9 M ⊙ based on the imagery and broadline velocity dispersion. Its synchrotron component peaks at the hard X-ray band during the bright state and moves to the soft X-ray band when the source gets fainter (Baloković et al 2016). During the faintest state in MJD 56302, its synchrotron component peaks at too low a frequency to make it similar to ISP/LSP.…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
See 3 more Smart Citations
“…Gorham et al (2000) estimated the central black hole mass of order ∼ 10 9 M ⊙ based on the imagery and broadline velocity dispersion. Its synchrotron component peaks at the hard X-ray band during the bright state and moves to the soft X-ray band when the source gets fainter (Baloković et al 2016). During the faintest state in MJD 56302, its synchrotron component peaks at too low a frequency to make it similar to ISP/LSP.…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
“…They found that this excess follows the extension of the γ-ray spectra well; therefore, they argued that this hard X-ray excess must be the low-energy part of the SSC emissions of the same electron population that is producing the Fermi/LAT γ-ray. Actually, the broadband SED at this epoch had been well fitted by a one-zone SSC model (up to the TeV band but except for the hard X-ray spectra; Baloković et al 2016). However, it can be seen that the observed hard X-ray excess cannot be reproduced by this one-zone modeling: the modeling underestimates the hard X-ray flux (upper left panel of Figure 13 in Baloković et al 2016).…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
See 2 more Smart Citations
“…Setup takes place during the day, the telescope performs all observations at night without operator assistance, and shuts down automatically at dawn. Over 30 students have been trained on it, while producing or contributing to approximately one refereed monitoring paper per year (e.g., [4][5][6][7][8][9][10]). …”
Section: Introductionmentioning
confidence: 99%